Knowledge, attitude, practice and stigma of tuberculosis among healthcare providers in hospital ampang - Shahbuddin H.M.A.-W.; Mahamad U.A.; Marwan A.A. (Universiti Putra Malaysia Press, 2024)
Indexed by SCOPUS/MYCITE